Una contradicción aparente en la formulación del exeundum en el § 42 de la Doctrina del derecho de Kant - Marey, Macarena (2014)
In this article, I analyze an apparent contradiction in Kant´s formulation of the "postulate of public right", in the § 42 of the Doctrine of Right, with the aim of studying Kant´s categorical foundation of the State. Taken at face value, the passage entails a contradiction because it states that [A] the practical necessity of the exeundum follows from private right, that is, from the problems posed by the state of nature, while at the same time it says that [B] the conceptual ground of the exeundum can be developed analytically from the concept of right, which Kant treats in a theoretical level systematically previous to the state of nature. First, I will analyze the statement [A] and try to clear up what "private right in the state of nature" means, reviewing -and rejecting- two possible constructions of it. The next step will be to study statement [B]. I will propose that this latter statement shows that the concept of right and the notion of juridical obligation attached to it are the ground of the inference that goes from "private right in the state of nature" to the "postulate of private right". Finally, I will advance the thesis that "private right in the state of nature" is the a priori condition of the categorical duty to leave the state of nature, as it serves to describe the normative consequences of the "situation of unavoidable coexistence", and that the "concept of right in external relations" is the normative criterion used to analyze that situation. In this way, statements [A] and [B] are both true and Kant´s formulation of the exeundum is no longer contradictory.